NICE DRINK MINUMAN BERBAHAN DASAR LOKAL KHAS DESA CISAAT KABUPATEN SUBANG - Mulyati; Muhammad Faesal; Jaka Marsita (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2022)
Abstract The 2022 Covid-19 pandemic has begun to subside, one of the countries that is actively voicing a movement for improvement is Indonesia through the tagline